2019
DOI: 10.1136/bmjopen-2019-028961
|View full text |Cite
|
Sign up to set email alerts
|

Association between nut intake and non-alcoholic fatty liver disease risk: a retrospective case-control study in a sample of Chinese Han adults

Abstract: ObjectivesNut consumption has been associated with a lower risk of type 2 diabetes, metabolic syndrome and insulin resistance. However, its effect on the risk of non-alcoholic fatty liver disease (NAFLD) is unknown. Therefore, we investigated the relationship between nut consumption and NAFLD risk.Setting and participantsWe conducted a retrospective case-control study including 534 patients diagnosed with NAFLD and 534 controls matched by sex and age (±5 years) from the Affiliated Nanping First Hospital of Fuj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 40 publications
3
28
0
1
Order By: Relevance
“…The association disappeared after adjusting for age, sex, waist circumference, homeostatic model assessment for insulin resistance, adiponectin, and tumor necrosis factor-α [38]. However, our findings are consistent with the results of a study by Chen et al [29], which failed to find a significant inverse relationship between high nut consumption and NAFLD risk among the overall samples. Interestingly, the current study indicated that compared to the first decile, higher consumption of nuts (in the deciles 9 and 10) was significantly associated with a higher risk of NAFLD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The association disappeared after adjusting for age, sex, waist circumference, homeostatic model assessment for insulin resistance, adiponectin, and tumor necrosis factor-α [38]. However, our findings are consistent with the results of a study by Chen et al [29], which failed to find a significant inverse relationship between high nut consumption and NAFLD risk among the overall samples. Interestingly, the current study indicated that compared to the first decile, higher consumption of nuts (in the deciles 9 and 10) was significantly associated with a higher risk of NAFLD.…”
Section: Discussionsupporting
confidence: 91%
“…The median intake of the highest frequency of nut consumption class in the Zhang et al study was 21.88 g/day [28]. Also, in Chen et al' study [29] the median of nut intake was 3.15 g/day in cases and 2.86 g/day in control group. Though most case-control studies showed protective effects on nut consumption on risk of NAFLD, high intake of nuts should be able to increase the prevalence of NFLD in other ways.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Among them, forty-seven articles were excluded because seven were review articles, eight were about adolescents, twenty-four were without the relevant exposure/outcomes and eight did not conform to the relevant study design. Finally, twenty-four articles were identified and included in this systematic review and meta-analysis (12)(13)(14)(15)18,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52) . The study selection process is described in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A total of five studies assessed the effect of nut consumption on the likelihood of NAFLD, which include two cross-sectional studies (with 4737 cases) and three case-control studies (with 768 cases) (15,34,35,39,51) . A negative association of nut intake with the possibility of NAFLD was observed among the cross-sectional studies (I 2 = 0 (Fig.…”
Section: Nutsmentioning
confidence: 99%